2022
DOI: 10.1186/s12954-022-00620-w
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported impacts of the COVID-19 pandemic among people who use drugs: a rapid assessment study in Montreal, Canada

Abstract: Background People who use drugs (PWUD) are at high risk of experiencing indirect harms of measures implemented to curb the spread of COVID-19, given high reliance on services and social networks. This study aimed to document short-term changes in behaviours and health-related indicators among PWUD in Montreal, Canada following declaration of a provincial health emergency in Quebec. Methods We administered a structured rapid assessment questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…We observed that a large proportion of participants (half of the women and one third of the men) who reported experiencing violence also reported an increase in the intensity of violence since the beginning of the COVID-19 pandemic. This finding is consistent with research showing individuals with a history of experiencing violence were more likely to be victimized during COVID-19 and PWUD experienced increased frequency of violence during COVID-19 [ 3 , 4 ]. Multiple consequences of the pandemic and related restrictions provide plausible explanations for intensification of violence: people may have endured increased exposure to violent relationships due to quarantine or physical distancing requirements [ 1 ]; access to support services or opportunities for refuge were curtailed, closed, or shifted online [ 17 ]; and heightened stress may have increased violence perpetration [ 3 , 5 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that a large proportion of participants (half of the women and one third of the men) who reported experiencing violence also reported an increase in the intensity of violence since the beginning of the COVID-19 pandemic. This finding is consistent with research showing individuals with a history of experiencing violence were more likely to be victimized during COVID-19 and PWUD experienced increased frequency of violence during COVID-19 [ 3 , 4 ]. Multiple consequences of the pandemic and related restrictions provide plausible explanations for intensification of violence: people may have endured increased exposure to violent relationships due to quarantine or physical distancing requirements [ 1 ]; access to support services or opportunities for refuge were curtailed, closed, or shifted online [ 17 ]; and heightened stress may have increased violence perpetration [ 3 , 5 ].…”
Section: Discussionsupporting
confidence: 91%
“…For instance, emerging research has indicated that the COVID-19 pandemic has exacerbated violent victimization among some priority populations, including women, children, and people who use unregulated drugs (PWUD) [ 3 – 5 ]. A recent rapid survey study found that over 29% of 227 PWUD surveyed in Montreal, Canada reported increased frequency of experiencing violence since the beginning of the pandemic [ 4 ]. Although there is limited published research describing factors impacting the experiences of violence of PWUD during the COVID-19 pandemic, in other priority populations (e.g., women), researchers have found links between financial insecurity due to the COVID-19 pandemic and a higher risk of physical mistreatment of children, as well as higher likelihood of intimate partner violence [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pre-pandemic trend of increasing naloxone kit and fentanyl test strip distribution remained stable during the peri-pandemic period despite the large reduction in total visits, suggesting that SCS and the community organisations that house them adapted rapidly to the pandemic context to maintain harm reduction material distribution. These findings are corroborated by a survey of people who use drugs in Montréal; the majority of participants who reported trying to access harm reduction services during the early pandemic period were able to do so ( Minoyan et al, 2022 ). Indeed, services and public health organisations in Montréal demonstrated remarkably rapid response to the large-scale disruption engendered by the COVID-19 pandemic, as evidenced by the relatively short-lived closure of SCS in the city ( Table 1 ).…”
Section: Discussionmentioning
confidence: 73%
“…While supervised injection sites and other services for people who inject drugs were disrupted, shifts were also reported in the availability, quality, and price of unregulated drugs ( Minoyan et al, 2022 ). Such shifts are often, but not always, associated with increased overdose risk ( Zolopa et al, 2021 ).…”
mentioning
confidence: 99%
“…Yet, it was not enough to cope with the needs due in part to the pandemic response (closure of or limited opening times of in-person substance use and harm reduction services) and the lack of harm reduction preparedness and reediness at the programming and system levels to cope with the surge of mental and social problems (e.g. isolation/lockdowns) or to ensure substance treatment continuity during first months of COVID-19 pandemic, in Toronto and across other Canadian jurisdictions [ 60 , 61 ]. Therefore, effective, coordinated, scalable harm reduction response planning should be strengthened to address substance use needs and prevent and mitigate associated harm across public emergencies and beyond.…”
Section: Discussionmentioning
confidence: 99%